PERSEPSI MAHASISWA TERHADAP PERUBAHAN NOMENKLATUR SURAT KEPUTUSAN (SK) IZIN PELAKSANAAN DARI PROGRAM STUDI MUAMALAH/EKONOMI PERBANKAN ISLAM KE MUAMALAH - Sri Rokhlinasari (Holistik, 2012)
This study aims to determine the perceptions and expectations of students about changing the nomenclature of the course name from Departement of Muamalah-Islamic Banking System to Departement of Muamalah at IAIN Syekh Nurjati Cirebon. This study uses a quantitative approach involving a student population of faculty of Sharia on related subjects. The aspects under research are student perception on the nomenclature name change of department, the impacts nomenclature on learning motivation of student and the impacts of the nomenclature name on curriculum. The results of this research are first, the overall attitude of the majority of respondents indicated that students chose the name, Muamalah-Islamic Banking System with a motivation of (1) needing to know the Islam-based economic activities, (2) needing to focus more on the banking / Islamic banking, (3) needing to implement Islamic economics and (4) needing to graduate from the department which has a bright prospect. Second, despite the nomenclature change of the name of the department, this does not affect to the declining motivation of students to learn. Third, yet, the curriculum developed in the course is still seen as inadequate.